A phosphoproteomic landscape of rice (Oryza sativa) tissues. Issue 4 (25th May 2017) - Wang, Yifeng; Tong, Xiaohong; Qiu, Jiehua; Li, Zhiyong; Zhao, Juan; Hou, Yuxuan; Tang, Liqun; Zhang, Jian
Abstract : Protein phosphorylation is an important posttranslational modification that regulates various plant developmental processes. Here, we report a comprehensive, quantitative phosphoproteomic profile of six rice tissues, including callus, leaf, root, shoot meristem, young panicle and mature panicle from Nipponbare by employing a mass spectrometry (MS)‐based, label‐free approach. A total of 7171 unique phosphorylation sites in 4792 phosphopeptides from 2657 phosphoproteins were identified, of which 4613 peptides were differentially phosphorylated (DP) among the tissues. Motif‐X analysis revealed eight significantly enriched motifs, such as [sP], [Rxxs] and [tP] from the rice phosphosites. Hierarchical clustering analysis divided the DP peptides into 63 subgroups, which showed divergent spatial‐phosphorylation patterns among tissues. These clustered proteins are functionally related to nutrition uptake in roots, photosynthesis in leaves and tissue differentiation in panicles. Phosphorylations were specific in the tissues where the target proteins execute their functions, suggesting that phosphorylation might be a key mechanism to regulate the protein activity in different tissues. This study greatly expands the rice phosphoproteomic dataset, and also offers insight into the regulatory roles of phosphorylation in tissue development and functions.